Hubungan antara Ekspresi P53 Mutan terhadap Operabilitas Kanker Serviks Stadium IIB Pasca Kemoterapi Neoajuvan - Arsyad, Nur Rohmah; Siswosudarmo, Risanto; Kusumanto, Ardhanu (JURNAL KESEHATAN REPRODUKSI, 2020)
Background: The therapy for stage IIB cervical cancer according to FIGO is concurrent chemoradiation. The neoadjuvant chemotherapy followed by radical hysterectomy is an alternative therapy to improve the survival rate of cancer patients. Cervical cancer is mainly caused by the infection of Human Papilloma Virus (HPV), which contains protein E6 and E7 that downregulate the apoptotic function of p53. The absent of p53 wild-type and the present of p53 mutation play roles on the cervical cancer pathogenesis.Objective: To analyze the association between the expression of mutant p53 to the stage IIB cervical cancer operability after neoadjuvant chemotherapyMethod: This study was a prospective cohort, using 40 of 67 patient who met eligibility criteria. The parafin block from cervical tissue were processed for immunohistochemical staining of p53 using Anti-mutant p53 antibody [Y5] ab32049, Abcam, USA. Two study groups were assessed as: 1) weak and 2) strong expression of mutant p53 expression after neoadjuvant chemotherapy based on H-score. Both group (weak and strong) were comparable in term of mutant p53 expression. In this study, the evaluation of operability was performed clinically. Age, BMI, histopathology, grade of differentiation, and regiment were also evaluated as the external variables. Chi square test, and logistic regression analysis were used for statistical analysis.Results and Discussion: The rate of cervical cancer operability after chemotherapy was 19 out of 40 (47.5%). The strong expression of mutant p53 was observed in 6 subjects (15%). There was no significant association between weak vs strong expression of mutant p53 to the operability of the cancer (RR 1.5, CI 95% 0.46-4.88, p 0.45). Multivariate analysis showed that combination (50 mg/m2 dan 5 fluorourasil 450 mg/m2) was significantly correlated the operability (OR 7.02, CI 95% 1.27-40.07, p 0.03). Conclusion: The expression of mutant p53 not correlate with operability after neoadjuvant chemotherapy, but combination regiment was.Keywords: expression of mutant p53, stage IIB of cervical cancer, neoadjuvant chemotherapy, operability